(untitled) (Journal of Human Sciences, 2020)
The Researcher has explained dialects role in the Holy Quran in helping know and facilitate Allah’s Will via call upon his worship , the researcher sees that Arab Dialects had a first echo in favor of the spread of Islam and its extraordinary eloquence that defeated the most eloquent orators since that time and until nowadays. We conceive that the language is more general and global than the dialect , but it is one of its part , also the Quran’s Readings are only known dialects before and after the Revelation of the Quran .In fact , Prophetical Hadiths have shown the great role in terms of dialects and their clarification , also , in easing and facilitating Holy Quran understanding with all its rules and teachings and related matters .